Factors contributing to prolonged turnaround time among patients receiving health services at Henrob Hospital Zana, Wakiso District. A cross-sectional study - Nowamani, Dismas; Nansereko, Hasifa; Nalubega, Jane Frank; Naggulu Posperia, Immaculate; Akankwasa, Edith (Student's Journal of Health Research Africa, 2025)
Background Variation in turnaround time has been evidenced in most healthcare facilities and becomes problematic if it exceeds thirty minutes. The purpose of this study was to determine the factors contributing to prolonged turnaround times among patients receiving health services at Henrob Hospital Zana in Wakiso District. Methodology The study design used was descriptive and cross-sectional. The study included both female and male patients receiving care at Henrob Hospital Zana. A sample size of 66 respondents was determined using the Krejcie and Morgan (1970) table. Participants were selected using a simple random sampling method. Data were obtained using a questionnaire, analyzed manually, and then automatically with the computer software Microsoft Excel 2013. The results were presented using tables, charts, and graphs. Results 66 respondents participated in this study, 47.0% were above 30 years of age, and 15% were single. Among individual-related factors, only 12.2% of patients who reported early were attended to urgently. In terms of healthcare-related factors, 30.3% of the respondents were new patients, while 59.1% were referral cases from other health facilities. Additionally, long turnaround times were most commonly associated with day duty, during which 54.5% of patients experienced prolonged waiting. Conclusion A smaller number of health workers, the economic status of patients, and the high number of patients attending the Henrob hospital Zana were among the factors that contributed to the turnaround time in the reception of health services at the hospital. Recommendation The Ministry of Health and hospital administration should advocate for the deployment of more health workers, close supervision of health workers, and the supply of equipment such as computers to reduce the time spent attending to patients.